The Difference between Mozart’s Classical Music and Preferred Music Therapy on Intensity of Menstrual Pain in Female Adolescents in 5 Senior High School of Denpasar - Ni Wayan Putri Perdana Sari (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2013)
Menstrual pain is the most often causes the absence of female adolescents in school or other activities. Distraction through music proved to show an effect in reducing pain. The selected music is instrumental music or Mozart’s classical music and also preferred music. This study aims to know the difference between Mozart’s classical music and preferred music therapy on the intensity of menstrual pain in female adolescents in 5 senior high school of Denpasar. This research is a quasy experimental. Samples consisted of 30 female adolescents who are selected by purposive sampling, divided into two groups, experimental groups (Preferred music) and control group (Mozart’s classical music). The results showed changes in the intensity of menstrual pain in female adolescents after had given the Mozart’s classical music that is 53.3% light and 46.7% moderate pain where the pain before was 53.3% moderate and 46.7% severe pain. The intensity of menstrual pain in female adolescents before had given the preferred music has the same percentage that was 53.3% moderate and 46.7% severe pain. The intensity of pain experienced by the percentage change of 40% is light and 60% is mild. Wilcoxon test is performed in both groups with value p <0.05, indicating both of Mozart’s classical music and preferred music affect menstrual pain intensity while the Mann Whitney test conducted concluded there was no significant difference between Mozart’s classical music with preferred music to the intensity of menstrual pain in female adolescents. Base on the above findings suggested to the school in order to use both of this music therapy to reduce the intensity of preferences menstrual pain that occurs in female adolescents at his school.